Improving the Efficiency of a Thermionic Energy Converter Using Dual Electric Fields and Electron Beaming - Bickerton, Ian; Fox, Neil A. (Frontiers in Mechanical Engineering, 2017)
Experiments have been conducted on a dual electric grid thermionic device to investigate an alternative method of space charge mitigation in a Thermionic Energy Convertor (TEC). Two electric grids, the attractor and deflector grids, provide opposing electric fields to overcome space charge while minimizing power losses to the attractor grid. Electron beams are formed in the electrode gap providing a more efficient electron transport from hot cathode to collector. The attractor gird can be run in DC or pulse mode which usefully supports transformer coupling for the energy convertor output. This is a simple low cost inter-electrode space charge solution running at low voltage which has the potential to improve TEC efficiency, increase reliability and reduce the cost of manufacture.